Enhancing Fiqih Learning Outcomes Through Renderforest Animated Video - Cecep Sobar Rochmat; Hanna Farida Haz (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to examine the effect of Renderforest-based animated video on students’ Fiqh learning outcomes by comparing post-test results between an experimental group taught using animated video media and a control group taught using conventional instructional methods. Methodology: This study employed a quantitative quasi-experimental approach with a posttest-only control group design. Renderforest software was used to develop animated video learning media. Data were collected through a post-test instrument. Statistical analysis was conducted using SPSS software, including normality testing, homogeneity testing, and the Mann–Whitney U test. Main Findings: The results showed a significant difference in students’ Fiqh learning outcomes between the experimental and control groups. Students who were taught using Renderforest-based animated videos achieved higher post-test scores than those taught using conventional methods. The Mann–Whitney U test indicated a statistically significant difference between the two groups (p < 0.001). Novelty/Originality of this study: This study offers novelty by specifically examining the effectiveness of Renderforest-based animated video media in Fiqh instruction through a quantitative quasi-experimental approach. Unlike previous studies that discuss animated videos in general, this research focuses on the Renderforest platform to present abstract Fiqh concepts contextually, thereby strengthening empirical evidence on digital instructional innovation in Islamic education.